An Evaluation on the Design and Content of a General English Textbook from the Students and Teachers’ Perspectives - Dwi Ratih Nolaputri (UM Purwokerto Press, 2023)
It cannot be denied that textbooks have a crucial role in ensuring the success of English language teaching and learning programs. Therefore, it is necessary to conduct evaluations to maintain the quality of the textbooks. This research aimed to find out the results of the evaluation on the design and content of the Intermediate level textbook for a General English course at a university in Purwokerto from both the students and teachers’ perspectives. This is a quantitative research with a survey procedure. Questionnaires were employed to obtain the data, and the data were analyzed using descriptive statistics method. The results show that the students were generally satisfied with the design and the content aspects of the textbook. On the contrary, the teachers expressed some dissatisfactions on some of those aspects. From the teachers’ perspective, the textbook needed some improvements in order to be categorized as a good textbook.